Penerapan Digital Marketing dalam Optimalisasi Pemasaran Jasa Pendidikan - Faiz, Romdhoni (Civiliza Publishing, 2023)
This article discusses the importance of digital marketing approach in marketing optimization of education institutions. The article highlights kinds of digital marketing components and its implementation in the marketing strategy, in order to increase its effectiveness and efficiency. The article also discusses seven variables in marketing mix namely products, price, place, promotion, people, process, and physical evidence. The article underlines the steps to formulate marketing strategy such as segmentation, targeting, and positioning, while keeping digital marketing mindset in discussing those. The research method used in this article is library research, which involves analyzing and synthetizing existing literature on the topic. The article concludes that having digital marketing approach is important to optimize the effectiveness and efficiency of education service marketing.